Implementasi Kelas Tahfiz Quran Masa Depan (TQ MD) di MTs Muallimin Univa Medan - Taufiq Hardiansyah; Khairuddin Lubis; Hasnah Siahaan (HIBRUL ULAMA, 2025)
In order to facilitate students who have greater memorization abilities, MTs Muallimin Univa Medan created a special class called the future tahfiz quran class. This class is gathered from grade VII students who have the best memorization abilities from other students and combined into one class called the future tahfiz quran class. This class has different tahfiz targets and programs from other classes. This study uses a descriptive qualitative approach implemented at MTs Muallimin Univa Medan. The subjects of this study are the future tahfiz quran class, and the sources are WKM in the curriculum field, tahfiz coordinator and tahfiz teacher of the future tahfiz quran class. The data collection techniques in this study use observation, interviews, and documentation. The data collected through the stages of data reduction, data presentation and drawing conclusions. The results of the study explain that the tahfiz quran class is a special class formed for students who have greater memorization abilities. Furthermore, the memorization program and objectives of this future Quran memorization class differ from those of other classes. The advantages of this class compared to other classes are the quantity of memorization, the quality of memorization, and the quality of recitation. However, the disadvantages and challenges encountered during the program's implementation are time allocation and the students' circumstances. Therefore, it can be concluded that this future Quran memorization class program can help students improve memorization and maintain the quality of their memorization and recitation.